Controlled dislocation density as enhancer of the magnetic response in multiferroic oxide nanoparticles. (December 2022) - Volnistem, Eduardo A.; Oliveira, Roger C.; Perin, Gabriel H.; Dias, Gustavo S.; de Melo, Mauricio A.C.; Cótica, Luis F.; Santos, Ivair A.; Süllow, Stefan; Baabe, Dirk; Litterst, F. Jochen
Highlights: Single phased nanostructured BFO is effectively synthesized by cryomilling. Crystallite size and dislocation density values are easily controlled. Nanoestructuration caused by cryomilling adds a superparamagnetic contribution. Uncompensated spins along the dislocation lines enhance BFO magnetic properties. Magnetic enhancements caused by nanostructuration and introduction of dislocations. Graphical abstract: Abstract: We report on the application of cryomilling for the synthesis of oxide ceramics nanoparticles with controlled dislocation densities using the rhombohedral BiFeO 3 compound as a model system. Multiferroic BiFeO 3 nanoparticles were prepared with controlled crystallite size, micro-strain and dislocation density. After milling for 150 min the average crystallite size is reduced to 23 nm, the levels of micro-strain increased to 1.2 % and the dislocation density reaches 1.7 × 10 13 cm − 2 . This shows that the cryomilling promotes the nanostructuration of the samples and the introduction of atomic defects such as dislocations. In addition we found an enhancement of the magnetic properties resulting from a combination of the presence of small nanoparticles and uncompensated spins along the dislocation lines. The isothermal magnetization measurements showed a weak-ferromagnetic behavior with 0.58 emu/g at 15 kOe at room temperature. Mössbauer spectroscopy ruled out the formation of Fe 2 + ions and also revealed the presence of a superparamagnetic contribution. The control of crystallite size along with dislocation density in BiFeO 3 is proposed as a powerful tool for tuning its magnetic properties.